2015
DOI: 10.1007/s00128-015-1693-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biochemical, Genetic and Hematological Biomarkers in a Commercial Catfish Rhamdia quelen Exposed to Diclofenac

Abstract: Juveniles Rhamdia quelen fish species were exposed to diclofenac for 96 h at concentrations of 0.2, 2, and 20 μg/L. Biochemical, genetic, and hematological biomarkers were assessed in the liver, kidney, and blood in order to evaluate the toxic effects. No oxidative stress was observed in liver. In kidney the superoxide dismutase activity increased in all concentrations, suggesting an alteration in the hydrogen peroxide production, but DNA damage and lipid peroxidation were not detected. Diclofenac exposure inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…Inflammatory reactions are common in fish, but the underlying mechanisms are poorly understood. In vivo exposure to diclofenac caused reduced counts of circulating leukocyte and reduced leukocyte migration [17]. Previous studies have shown that diclofenac exposure reduced nitric oxide production in primary cultures of leukocytes [16].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Inflammatory reactions are common in fish, but the underlying mechanisms are poorly understood. In vivo exposure to diclofenac caused reduced counts of circulating leukocyte and reduced leukocyte migration [17]. Previous studies have shown that diclofenac exposure reduced nitric oxide production in primary cultures of leukocytes [16].…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have shown that diclofenac exposure reduced nitric oxide production in primary cultures of leukocytes [16]. In vivo exposure to diclofenac caused reduced counts of circulating leukocyte and reduced leukocyte migration [17]. Diclofenac also increased hepatic oxidative stress [18] in Hoplias malabaricus.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The pharmaceutical agent diclofenac is concluded to induce oxidative stress on the common carp C. carpio, with the highest incidence of oxidative damage occurring in liver and gill. Acute exposure to diclofenac, even at low concentrations, caused hematologic and renal enzymatic alterations in R. quelen [22]. When Cyprinus carpio was exposed to diclofenac and clofibric acid, it was found that there were significant changes [23].…”
Section: Hplc Analysis Of Diclofenacmentioning
confidence: 98%